Tension Pneumoperitoneum Following Diagnostic Colonoscopy Presenting as a Lethal Abdominal Compartment Syndrome - Sayida, Sa'd; Hallon, Kenan; Mansour, Subhi; Khuri, Safi (Archives of Clinical and Medical Case Reports, 2019)
Introduction: Nowadays, colonoscopy has become a very common procedure used to evaluate different colonic pathologies. Complications following this procedure are usually rare, with perforation being the most dreaded and severe one. An infrequent, yet potentially life-threatening complication of colonic perforation is abdominal compartment syndrome (ACS), due to continuous elevation of intra-abdominal pressure as a result of iatrogenic perforation. Case Presentation: Herein, we report a case of a 73-year-old female patient, who presented to our Emergency Medicine department with abdominal pain and distension, hypotension and respiratory distress following diagnostic colonoscopy. An upright Chest x-ray revealed free air under the diaphragm, and the patient admitted with a diagnosis of abdominal compartment syndrome due to colonic perforation following diagnostic colonoscopy. On exploration of the abdomen, a 2 cm tear of the antero-medial wall of the cecum was demonstrated and an abbreviated laparotomy with right hemicolectomy and temporary closure of the abdomen was performed. Several hours following surgery, the patient developed multi-organ failure and died. Conclusion: Abdominal compartment syndrome due to perforation after colonoscopy is an extremely rare condition, and a high index of suspicion is warranted for prompt early diagnosis and treatment.